1994
DOI: 10.1104/pp.105.1.35
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Specific Expression of a Gene Encoding a Cell Wall-Localized Lipid Transfer Protein from Arabidopsis

Abstract: Nonspecific lipid transfer proteins (LTPs) from plants are characterized by their ability to stimulate phospholipid transfer between membranes in vitro. However, because these proteins are generally located outside of the plasma membrane, it is unlikely that they have a similar role in vivo. As a step toward identifying the function of these proteins, one of severa1 LTP genes from Arabidopsis has been cloned and the expression pattern of the gene has been examined by analysis of the tissue specificity of 8-glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
175
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(188 citation statements)
references
References 37 publications
(47 reference statements)
12
175
1
Order By: Relevance
“…2I). In F 1 seedlings, the GUS pattern did not differ from the reported LTP1::GUS pattern (Thoma et al, 1994; data not shown), and analysis of GFP fluorescence revealed strict epidermal specificity (Fig. 2, J and K).…”
Section: Reliable Domain-specific Reporter Gene Expression After Mgalmentioning
confidence: 86%
See 1 more Smart Citation
“…2I). In F 1 seedlings, the GUS pattern did not differ from the reported LTP1::GUS pattern (Thoma et al, 1994; data not shown), and analysis of GFP fluorescence revealed strict epidermal specificity (Fig. 2, J and K).…”
Section: Reliable Domain-specific Reporter Gene Expression After Mgalmentioning
confidence: 86%
“…The Arabidopsis RPS5A (RIBOSOMAL PROTEIN S5A) promoter is strongly expressed in dividing cells, starting as early as the one-cell embryo stage (Weijers et al, 2001a). The Arabidopsis LTP1 (LIPID TRANSFER PROTEIN 1) promoter marks the L1 layer of all newly formed organs and is preferentially expressed in the apical domain of the embryo (Thoma et al, 1994). The synthetic auxin-responsive DR5(7x) promoter has an expression peak in the central root cap cells of the torpedo stage Arabidopsis embryo (Sabatini et al, 1999).…”
Section: Plant Lines For Conditional Domain-specific Expression In Sementioning
confidence: 99%
“…To further analyze the requirement for GNOM in the epidermis, we expressed GNOM from an epidermis-specific promoter in the gnom mutant background. The LIPID-TRANSFER-PROTEIN1 (LTP) promoter is exclusively expressed in the epidermis once the protoderm is formed (Thoma et al, 1994;Baroux et al, 2001). Driving GNOM from this promoter did not result in a discernible rescue phenotype, but introducing the LTP driver construct into the ANT>>GNOM background (LTP+ANT>>GNOM) led to a significant increase in the proportion of rescue phenotypes that showed a complete apical rescue with bilaterally symmetrical spacing of the cotyledons and a corresponding reduction of fusedcotyledon rescue phenotypes (see Table S1B in the supplementary…”
Section: Radial-to-bilateral Symmetry Transition Requires Protodermalmentioning
confidence: 99%
“…The LTPs so far cloned contain a leader sequence responsible for insertion into the ER and subsequent secretion of the protein (Bernhard et al, 1991;Madrid, 1991). In situ hybridizations have shown accumulation of Itp transcripts in epidermal layers of tobacco (Fleming et al, 1992), tomato (Fleming et al, 1993), and Arabidopsis (Thoma et al, 1994), and anti-LTP antibodies recognized epitopes in cell walls and intercellular spaces in Arabidopsis (Thoma et al, 1993). Furthermore, in broccoli, LTP is the most abundant protein in the extracellular wax (Pyee andKolattukudy, 1994, 1995).…”
mentioning
confidence: 99%
“…Such a specific localization of LTP in the epidermal cell wall is incompatible with a role in general lipid redistribution, and, in the light of a11 these observations, LTPs have been proposed to play a role in the transport of extracellular lipophilic material. This material could be required for the assembly of cutin (Sterk et al, 1991) and other amorphous barriers around the plant (Koltunow et al, 1990;Sossountzov et al, 1991;Kalla et al, 1994;Thoma et al, 1994).…”
mentioning
confidence: 99%